Reading Republican oratory reconstructions, contexts, receptions - Gray, Christa 1982-; Balbo, Andrea 1970-; Marshall, Richard M. A. 1983-; Steel, Catherine E. W. 1973- (Oxford University Press, 2018)
Public speech was a key aspect of politics in Republican Rome, yet the partial nature of the available evidence means that our understanding of its workings is dominated by one man: Cicero. This volume explores the oratory of the Roman Republic as practiced by individuals other than Cicero, focusing on the surviving fragments of such oratory
This edition previously issued in print: 2018. - Includes bibliographical references and index
Keywords: Geschichte 470 v. Chr.-27 v. Chr.; Speeches, addresses, etc., Latin; Oratory / Rome; Rhetorik; Rede; Römisches Reich; Konferenzschrift -- 2015 -- Turin